Hambatan Pengajuan Klaim Asuransi Jiwa Disebabkan Kelalaian Pihak Pemegang Polis Terkait Dengan Kewajiban Pemberitahuan Riwayat Kesehatan (Studi Putusan Badan Penyelesaian Sengketa Konsumen Nomor : 005/BPSK-TT/KEP/IV/2016) - Nanda Lucya Gultom; Hasim Purba; Sunarmi Sunarmi; Dedi Harianto (Iuris Studia: Jurnal Kajian Hukum, 2021)
Honest information from the Insured is one of the conditions that must be met before an insurance agreement is known as the "principle of good faith". One form of violation of this principle is hiding facts about the Insured's personal health by dishonestly conveying information contained in the Consumer Dispute Settlement Arbitration/Mediation Decision Number: 005/BPSK-TT/KEP/IV/2016 issued on April 14,2016 which is the discussion in this study. The formulation of the problem in this study are: how is the regulation regarding the obligation to notify health history in life insurance, what are the obstacles that will occur in submitting a life insurance claim if the policyholder commits negligence related to the obligation to notify health history and how is the analysis of BPSK legal considerations on the cancellation of the letter. rejection of claims made by the Insurance Company against the submission of a death claim (Study of the Decision of the Consumer Dispute Settlement Agency Number: 005/BPSK-TT/KEP/IV/2016). This research method uses a descriptive normative juridical approach. The data used are primary data, namely secondary data collected by library research and interview results. All data were analyzed by qualitative data analysis method. Based on the research, the regulation regarding the Obligation of Notification in Insurance is stated in Article 52 of the Financial Services Authority Regulation Number: 23/POJK.05/2015 concerning Insurance Products and Marketing of Insurance Products and in Article 251 of the Commercial Code (KUHD). Obstacles that occur in the filing of a Life Insurance Claim Due to the Negligence of the Policyholder Regarding the Obligation of Health History Notification is the non-disbursement of the sum insured or called Claim Rejection. Analysis BPSK's legal considerations regarding the cancellation of the claim rejection letter made by the insurance company against the submission of a death claim in the decision are that there are several things that are wrong in the BPSK judge's analysis in the form of discrepancies between legal facts and the chronology of the case